Plant growth promoting rhizobacteria in promoting sustainable agriculture - V. Dhayalan; K. Sudalaimuthu (Global Journal of Environmental Science and Management)
Rapid human population growth and its consequences of food shortage become a significant concern in recent decades across the world. The untold reasons behind this food shortage were industrialization, urbanization, modern civilization, etc., where the agricultural land has been deployed. With the decreasing farmland and its cultivation, food productivity declined drastically and failed to serve the world's vast human population. The present challenge is to increase productivity with the least agricultural land. Thus, excessive chemical fertilizer has been used to quickly turn out more outstanding food production, leading to more significant damages to soil ecosystem and human health. Henceforth, bio-fertilizers find the best alternatives to chemical fertilizers. This study focuses on complete nature of plant growth Promoting rhizobacteria, which is used in bio fertilizers for sustainable agricultural productivity and everlasting soil fertility. The characteristics of plant growth promoting rhizobacteria and its role in plant growth and formulation of plant growth promoting rhizobacteria biofertilizers have been revealed through intensive literature. The consortium information collected from various literatures brings the unique findings that plant growth promoting rhizobacteria is the natural boon to the global agriculturist. This study discusses plant growth promoting rhizobacteria bacterial strains' role in protecting the soil from various biotic and abiotic stresses, regulating plant growth and its role in producing biofertilizers. Besides, it is transformed into commercial products. Eventually, the future trends and research in plant growth promoting rhizobacteria bio inoculants that promote sustainable agriculture have been elucidated. The microorganism is the bio fertilizer's main ingredients, promoting the soil nutrients for efficient plant growth and increasing food productivity. Although many microorganisms efficiently contribute to the soil nutrients, this review narrows down to the plant growth promoting rhizobacteria study. Beneficial bacterium plays a vital role in nutrient mineralization and productivity among the various microorganisms. Bio fertilizers containing beneficial bacteria were economically viable and readily available in nature. This review reveals the complete essence of plant growth promoting rhizobacteria and its part in bio fertilizers. ==========================================================================================COPYRIGHTS©2021 The author(s). This is an open access article distributed under the terms of the Creative Commons Attribution (CC BY 4.0), which permits unrestricted use, distribution, and reproduction in any medium, as long as the original authors and source are cited. No permission is required from the authors or the publishers.==========================================================================================